COMPUTER SCIENCE TEACHING OF SCIENCE IN INFORMATION-METHODICAL IMPROVEMENT TOOLS - Toshpulatov Rakhimjon Ismailovich (Galaxy International Interdisciplinary Research Journal, 2023)
In order for the teacher to effectively apply digital educational resources in the educational process, first of all, attention should be paid to the appropriate software. Obviously, training by highly qualified specialists: psychologists, science teachers, computer designers and programmers, it is necessary to work together to develop software products intended for the educational purpose. Many large foreign firms and a number of domestic software product manufacturers finance computer learning systems, digital educational resource creation projects in educational institutions and are making their own developments in this area.